2012
DOI: 10.1007/s00280-012-1883-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase II and gene expression analysis trial of neoadjuvant capecitabine plus irinotecan followed by capecitabine-based chemoradiotherapy for locally advanced rectal cancer: Hoosier Oncology Group GI03-53

Abstract: This neoadjuvant regimen was safe and demonstrated significant antitumor activity. High TP tumor gene expression was associated with obtaining pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
13
1
1
Order By: Relevance
“…Given the small numbers of patients, and the overall limited efficacy of the capecitabine regimen, it is difficult to determine association of TYMP , TYMS , and DPYD with response. Higher levels of TYMP have been associated with higher rates of pathological response to preoperative capecitabine or 5‐FU in colorectal cancer , and to prolonged time to progression from capecitabine in metastatic breast cancer , but in this study, there did not appear to be a trend with baseline TYMP and clinical, radiographic, or Miller–Payne response. However, as noted, it is difficult to draw conclusions with the small numbers of patients in each response group.…”
Section: Discussioncontrasting
confidence: 74%
“…Given the small numbers of patients, and the overall limited efficacy of the capecitabine regimen, it is difficult to determine association of TYMP , TYMS , and DPYD with response. Higher levels of TYMP have been associated with higher rates of pathological response to preoperative capecitabine or 5‐FU in colorectal cancer , and to prolonged time to progression from capecitabine in metastatic breast cancer , but in this study, there did not appear to be a trend with baseline TYMP and clinical, radiographic, or Miller–Payne response. However, as noted, it is difficult to draw conclusions with the small numbers of patients in each response group.…”
Section: Discussioncontrasting
confidence: 74%
“…In the present study, 55% of advanced tumors demonstrated high cytoplasmic expression of CES2. CES2 overexpression has been associated with increased irinotecan activity in vitro , even if its clinical relevance is less well determined [ 14 ]. Recently, Uchida et al .…”
Section: Resultsmentioning
confidence: 99%
“…In light of these findings, we suggest that Topo-I expression together with TS expression [ 14 ] could be associated with metastatic progression of CRC. TS expression correlates with clinical outcome of mCRC patients treated with a first-line FOLFIRI regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Irinotecan has also been employed in ovarian (76), non-small lung cell (77) and pancreatic and biliary tract cancers (78). Irinotecan is prescribed alone, or combined with: i) 5-fluorouracil and Leucovorin (FOLFIRI), ii) FOLFIRI plus oxaliplatin, iii) Cetuximab, a chimeric immunoglobulin G1 anti-epidermal growth factor receptor monoclonal antibody (37,79), or iv) capecitabine (80). The combined effects of the genetic variants in these drug-metabolizing enzymes need to be considered to reduce undesirable effects and to increase the effectiveness of the drugs.…”
Section: Examples Of Ugt1a Involvement In Pharmacogenomicsmentioning
confidence: 99%